Interim Restorations in Fixed Prosthodontics: A literature review - Raghad S. Jamel; Eman M. Yahya (University of Mosul, College of Dentistry, 2022)
Background: Interim or transitional restorations have been demonstrated as critical components in different dental treatments, they designed to enhance the esthetics, functions and protect the oral structures for limited period of time. Aims: This review focuses on several important aspects associated with the interim restorations including: materials, techniques of fabrication, and current trends in the application of interim restorations in fixed prosthodontics. Conclusions: Interim fixed restorations play a specific role in the diagnosis and treatment plan of the dental procedures. They must resemble the function and form of the definite prostheses. Therefore, interim restorations should satisfy the criteria of longevity, marginal adaptation and strength.